Religion and Identity in South Asia and Beyond: Essays in Honor of Patrick Olivelle, edited by Steven E. Lindquist - Cecil, Elizabeth (Religions of South Asia, 2016)
Religion and Identity in South Asia and Beyond: Essays in Honor of Patrick Olivelle, edited by Steven E. Lindquist. Cultural, Historical and Textual Studies of Religions; New York: Anthem Press, 2011. 392 pp., £60 (pb). ISBN 978-1-78308-067-0 (pb).